Radiation Therapy Oncology Group Gynecologic Oncology Working Group: Comprehensive Results. Issue 5 (1st June 2014) - Gaffney, David K.; Jhingran, Anuja; Portelance, Lorraine; Viswanathan, Akila; Schefter, Tracey; Weidhaas, Joanne; Small, William
Abstract : Abstract: The purpose of this report was to comprehensively describe the activities of the Gynecologic Oncology Working Group within the Radiation Therapy Oncology Group (RTOG). Clinical trials will be reviewed as well as translational science and ancillary activities. During the past 40 years, a myriad of clinical trials have been performed within the RTOG with the aim of improving overall survival (OS) and decreasing morbidity in women with cervical or endometrial cancer. Major study questions have included hyperbaric oxygen, neutron radiotherapy, altered fractionation, hypoxic cell sensitization, chemosensitization, and volume-directed radiotherapy. RTOG 7920 demonstrated improvement in OS in patients with stages IB through IIB cervical carcinoma receiving prophylactic para-aortic irradiation compared to pelvic radiation alone. RTOG 9001 demonstrated that cisplatin and 5-FU chemoradiotherapy to the pelvis for advanced cervix cancer markedly improved OS compared to extended field radiotherapy alone. More recent trials have used radioprotectors, molecular-targeted therapy, and intensity-modulated radiation therapy. Ancillary studies have developed clinical target volume atlases for research protocols and routine clinical use. Worldwide practice patterns have been investigated in cervix, endometrial, and vulvar cancer through the Gynecologic Cancer Intergroup. Translational studies have focused on immunohistochemical markers, changes in gene expression, and miRNA patterns impacting prognosis. The RTOG gynecologic working group has performed clinical trials that have defined the standard of care, improved survival, and added to our understanding of the biology of cervical and endometrial cancers.